Development of Nego Book Learning Media Based on Assemblr Edu To Improve Negotiation Text Speaking Skills - Sari, Shinta; Mindaudah; Resti Wahyuniarti , Fitri; Sulistyowati , Heny (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to develop learning media based on Assemblr Edu to improve students’ speaking skills in negotiation texts. This research employs the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through expert validation, observation, questionnaires, interviews, as well as pre-test and post-test. The results of expert validation indicate that the developed media is highly feasible for use, with an average score above 90% based on content, presentation, and functionality aspects. The effectiveness test results show an increase in students’ average scores from 60.25 in the pre-test to 89.17 in the post-test. The paired sample t-test analysis yields a significance value of p = 0.000 (p < 0.05), indicating that this media is effective in improving students’ learning outcomes. In addition, students’ responses show that the media is engaging, easy to use, and capable of enhancing motivation and confidence in the learning process. Therefore, Assemblr Edu-based learning media has been proven effective in supporting negotiation text speaking skills and has the potential to serve as an innovative reference in technology-based learning development.